Employee Perception on Merger and Acquisition of Commercial Bank in Nepal - Rayamajhi Sushma (Journal of Corporate Finance Management and Banking System, 2024)
The merger and acqisition of commercial banks can have significant impact on employee perception of their job security, working condition and remuneration. This paper examine level of satisfaction in term of job security among the employees of mergred and acquired, level of satisfaction in term of pay among the employees of mergred and acquire and level of satisfaction in term of working condition among the employees of mergred and acquired.20 questionnaire is distributed among employee of mergered and acquired commercial bank of Nepal.The purpose of the study is to fulfill the research gap and try to analyze the relationship between dependent variables and independent variables such as jobsecurity,working condition and Remuneration.Judgemental sampling technique is used to conduct the survey among 100 employee of banking sectors.Data collection period of this paper is 2 month.Multiple Regression analysis is used for Data Analysis procedures. Major conculsion of this paper is that there is positive but insignificance relationship between job security and employee perception. There is positive and significance relationship between working condition and remuneration.